2014
DOI: 10.1007/bf03396917
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glucose Consumption on Customers’ Price Fairness Perception

Abstract: Price fairness research has not yet developed a comprehensive explanation of what drives customers' perception of price fairness. Here, we show that customers perceive product prices as having greater fairness after glucose intake, thus identifying a biological driver of customer price fairness perception. We also show that there is no linear effect of glucose consumption on customers´ price fairness perception, and that glucose intake does not lead to significant differences in the mood states of participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 118 publications
1
4
0
Order By: Relevance
“…Thus, it can conclude that the right price and excellent service quality affect the level of customer satisfaction. This statement strengthens in a study conducted by Linzmajer, Hubert, Eberhardt, Fojcik & Kenning (2014).…”
Section: Frameworksupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, it can conclude that the right price and excellent service quality affect the level of customer satisfaction. This statement strengthens in a study conducted by Linzmajer, Hubert, Eberhardt, Fojcik & Kenning (2014).…”
Section: Frameworksupporting
confidence: 82%
“…Simultaneously, the remaining 38.0% are the other variables that not examine, such as promotion, location, distribution, value, and others. The finding is following Linzmajer, Hubert, Eberhardt, Fojcik & Kenning (2014), price and quality have a significant influence on consumer satisfaction.…”
Section: Resultsmentioning
confidence: 83%
“…Based on our results and previous research findings (McCormick et al, 1992 ) it should therefore be evident that mobile fNIRS is not always a suitable neuroimaging method or even a panacea; and cannot be applied when the research focus relies on, for example, subjacent brain regions. An example in this regard might be the measurement of emotional and perception processes such as price (fairness) perception (Knutson et al, 2007 ; Linzmajer et al, 2014 ). Given the fact that emotional and perception processes find its neural origin in “deeper” brain regions such as e.g., the hippocampus, the insula, the nucleus accumbens and/or the amygdala, mobile fNIRS with its technical capabilities, might currently not be able to shed light on these processes.…”
Section: Mobile Fnirs—a Validated Neuroimaging Method?mentioning
confidence: 99%
“…Building upon neuroscience research bearing on food as a motivated choice, we elaborate a conceptual framework (see Figure 1) focusing specifically on the single and compounded effect of the MS of food and the MS of marketing activities (in-store display and price) and hypothesize the impact on weekly product sales. Consumer neuroscience is recognized for its ability to represent better the impact of marketing on consumers’ decision-making and shed light on novel research variables (Chen et al , 2015; Gier et al , 2020; Krampe et al , 2018; Linzmajer et al , 2014; Lee et al , 2018; Meyerding and Mehlhose, 2020; Plassmann et al , 2012; Plassmann et al , 2015; Yoon et al , 2012). For example, research studying the dopaminergic system found that, contrary to common belief, in the presence of consumption cues such as food sampling, consumers tend to pursue further rewarding goals such as eating rather than satiating and reducing engagement in the behavior (Wadhwa et al , 2008; Yoon et al , 2012).…”
Section: Conceptual Framework and Research Hypothesesmentioning
confidence: 99%
“…Both human and animal experiments usually use sugared water as a primary reward reinforcer (McClure et al , 2004). For example, Linzmajer et al (2014) linked consumers’ price fairness with biological drivers, where after glucose intake, consumers perceived greater price fairness.…”
Section: Conceptual Framework and Research Hypothesesmentioning
confidence: 99%